THE IMPACT OF FX (FOREIGN CURRENCY EXCHANGE) ON THE BOTTOM LINE OF TEXTILE/SHOES INDUSTRIES LISTED IN INDONESIA STOCK EXCHANGE 2006-2008 - Subekti, Hendro (Journal of Indonesian Economy and Business, 2010)
During 2006-2008, Indonesia has been experiencing depreciation of IDR against worldÂ currency US$. The situation was triggered by global crisis October 2008, and IDRÂ currency plunged. Furthermore, 17 textile/shoes industries publicly listed in ISX have beenÂ severely hit by depreciation of IDR The âHuge Loss of Bottom Lineâ in 2008 was recordedÂ (IDR 617 billions) more than half of trillion IDR. To be curious the most of industry areÂ manufacturer-exporter.Year 2007, national textile industry overwhelmingly reports the export sales of US$Â 10.05 billion and the raw material import was US$ 2.04 billions. By these facts, IncomeÂ contribution from textile/shoes industries sector was US$ 8.01 billion and became a mileÂ stone of the achievement. Depreciation of IDR currency is an advantage to the exporter asÂ product become cheaper for foreign buyer while import goods costly to foreign seller.The aim of this research is to describe the impact of FX on the bottom line of theÂ Textile/Shoes Industries listed in ISX during 2006-2008, a period when the profitÂ performance has been fallen sharply in line with the depreciation of IDR currency. ByÂ using the mathematical regression equation is surprisingly proven that FX adverselyÂ impact to the âbottom lineâ of the industry. The equation model selected Net Income asÂ dependent variable while Operating Profit, Financial Charges and FX (Forex) as theÂ independent variable.From the outcome of the research, the dilemma between operation and financialÂ leverage is revealed. Depreciation IDR was negatively reduced the âbottom lineâ this wasmainly due to higher FX loss. By the end of December 2008, 17 shoes/textile industriesÂ have been suffered a huge loss of FX, and recorded FX Loss (IDR 564 billions), inÂ connection with âhigh financial leverage denominated in US$ currencyâ. The snapshot of balance sheet position is called âNet Short Asset to US $â. Only 5 Industries were makingÂ money among 17 industries during 2008. Only one company had already âhedgedâ theirÂ exposure to FX. Only one company who reported profit show âdebt to equity ratioâ isÂ much lower than average industry (US Textile Manufacturing)Â However, under the operational expectation, the depreciation of IDR currencyÂ encourage better performance of âexport oriented companyâ. This is the dilemma thatÂ textile/shoes industries have been exposed to financial risk in one side and on the otherÂ side operational risk (competitiveness).Keywords: net short asset to US$, financial leverage and financial risk, operational risk,Â foreign exchange loss, depreciation of IDR.